PENGARUH LUBANG PADA INTI KOLOM TERHADAP DAKTALITAS - Sultan, Mufti Amir (Program Stud Teknik Sipil Fakultas Teknik Universitas Khairun, 2015)
Conduits (pipes) in reinforced concrete columns is still use to date. SNI 03-2847-2002 Code limits upto 4% of the column cross section. But the codes does not mention the effect of the hollow cross sectionductility.This study was done by testing hollow and solid column with four variation, column crosssection b=h= 200 mm x 200 mm, column length L = 1.500 mm, hole ratio (0%; 3,32%; 5,68%;12,31%), single stirrup. End of the column are loaded by conctant axial compression 5,0 ton, lateralload are applied at Ã‚Â½ span until ultimate strength. The observed variables are lateral load anddeflection.The result of the study shows momen strength hollow column experience is decline 4,04%at hole ratio 3,32%; 7,99% at hole ratio 5,68% and 21,66% at hole ratio 12,31%. Ductility for columnwith hole ratio 3,32% and solid column same asumed.The experiment also indicates ductility withinrange of 7.683